Effects of conditioning programme on the changes of motor performance in youth categories in handball - Priklerová, S. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2018)
The ability to perform the stable playing performance during the whole match to larger extent depends on sufficient level of development of conditioning abilities. Technique of playing activities of an individual, decision-making process of players and especially speed of the game are influenced by already mentioned abilities. The aim of our study was to recognize the level of motor performance in regional centres of handball and at the same time to verify the efficiency of sports preparation. This programme includes the change of weekly microcycle practice, consisting of 2 conditioning trainings focused on strength and endurance. The research was realized in these age categories: younger (n=40) and older juniors (n=38). To evaluate the level of motor abilities we selected 5 simply performed activities: bench press (explosive strength of upper extremities ), run for 8x5 metres (speed with change of direction), sit-ups for 2 minutes (power of abdominal muscles), standing long jump with legs together (explosive strength of lower extremities) and 12 minutes run (aerobic endurance). When following microcycle programme weekly, the results of motor test pointed out the positive influence of this programme on the development of strength and aerobic endurance (p=0.05). In category of older juniors the performance in test of 12 minutes run has fallen significantly in comparison with the first testing (p=0.05). The result of this study indicates the lack of recommended aerobic running practice in weekly microcycles of monitored teams.